SISTEM PENUNJANG KEPUTUSAN PEMILIHAN SUPPLIER BESI MENGGUNAKAN METODE SAW (SIMPLE ADDITIVE WEIGHTING) - Edward Edward; Dedi Trisnawarman; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
Sukses Makmur  was established in 2004. t to fulfill the needs meet in the Store, Owner (owner) usually perform manual selection of iron that is by seeing thickness, length, and price by naked eye. This causes the owner to feel difficulty in determining the appropriate supplier with the criteria.This Program use to create a Decision Support System to determine the best iron supplier based on assessment criteria. In the data collection method used is observation and interview, for research method used is SDLC (System Developtment Life Cycle) method, and the method used in writing this thesis is Simple Additive Weighting (SAW) method. SAW method is used for e assessment of iron suppliers. The results obtained are Decision Support Systems that can assist shopkeepers in determining the best supplier ratings.